2005
DOI: 10.1177/019874290503000201
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcomes for Positively and Negatively Discharged EBD Students from Nonpublic Special Education Facilities

Abstract: This paper presents results from a study initiated by a consortium of non-public special education facilities to respond to issues of accountability. Research questions were (a) How do students from the most restrictive therapeutic non-public special education facilities compare with other nationally published studies?; and (b) How do positive and negative discharge students differ in transition experiences after leaving a restrictive therapeutic nonpublic special education facility? Three cohorts of EBD stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Again, while Tier 2 is necessary for this smaller group of nonresponsive students, it will be insufficient to prevent failures among a smaller group of students, generally approximating about 5% of the population. The third, and most intensive, tier provides individualized academic and behavioral interventions and supports for this expected smallest group of students whose continued failures put them at serious risk for eventual school exclusion and drop out (Carran, Kerins, & Murray, 2005). As a framework, PBIS acts as a mechanism for identifying those students who have not been responsive to prevention efforts and provides increasingly more intensive interventions to promote maximum success across all students.…”
mentioning
confidence: 99%
“…Again, while Tier 2 is necessary for this smaller group of nonresponsive students, it will be insufficient to prevent failures among a smaller group of students, generally approximating about 5% of the population. The third, and most intensive, tier provides individualized academic and behavioral interventions and supports for this expected smallest group of students whose continued failures put them at serious risk for eventual school exclusion and drop out (Carran, Kerins, & Murray, 2005). As a framework, PBIS acts as a mechanism for identifying those students who have not been responsive to prevention efforts and provides increasingly more intensive interventions to promote maximum success across all students.…”
mentioning
confidence: 99%
“…Place, Wilson, Martin, and Hulsmeier (2000) found that among a sample of youth with emotional disturbance ages six to 13, 24% were diagnosed with depression, 11% were diagnosed with anxiety disorders, and 70% were diagnosed with ADHD. Youth with ED also have a high risk of developing mental health disorders in adult life (Carran, Kerins, & Murray, 2005;Kovacs, 1997;Newman et al, 1996;Place, et al, 2000;Rutter, 1985).…”
mentioning
confidence: 99%
“…Kevin, and his care-providers, reported that he was having a difficult time making friends who were at his age level, which reflected difficulties with Kevin's social identity development. Adolescents who live with peers with ED often have poor relationships with others in their age group (Carran et al, 2005;Place et al, 2000;Brownfield & Thompson, 1991). Kevin stated that he tended to hang around the staff members, and he considered many of them to be his friends.…”
mentioning
confidence: 99%